The Zechariah tradition and the gospel of Matthew - Moss, Charlene McAfee (Zeitschrift für die neutestamentliche Wissenschaft / Beihefte, 2008)
Introduction: Matthew's use of Scripture traditions -- Recent studies on Matthew's "use of Biblical tradition" -- The form of Matthew's sources -- Methodology -- Jesus, the newborn king : Davidic branch, Savior, Emmanuel, Nazarene (Matthew 1:18-25; 2:1-6, 23; Zechariah 6:12; 8:7, 11-13, 20:23; 9:16) -- Matthew 1:18-25 -- Matthew 2:1-2 -- Matthew 2:3-6 -- Matthew 2:23 -- Jesus' ministry in Galilee : the Healing Shepherd (Matthew 9:36; Zechariah 10:2) -- Jesus' entry into Jerusalem : the humble Messianic King (Matthew 21:5 (11:25-30); Zechariah 9:9 (14:4-5)) -- Christology in Matthew 11:25-30 -- Excursus one: wisdom christology and Matthew 11:25-30 -- Excursus two: the Palm Sunday donkey -- Jesus in the temple : the prophet from Nazareth in Galilee (Matthew 21:12-16; Zechariah 14:21) -- Jesus and Zechariah : the blood of Zechariah, son of Barachiah, in the temple (Matthew 23:35; Zechariah 1:1-7) -- Jesus, the Son of Man : the Matthean apocalypse (Matthew 24:27, 30-31, 36-44, 25:31; Zechariah 2:6(10); 9:14; 12:10; 14:4-7) -- Jesus' blood of the covenant : forgiveness of sins (Matthew 26:28; Zechariah 9:11) -- Jesus, the stricken shepherd : the prophecy fulfilled (Matthew 26:31; Zechariah 13:7) -- Jesus and the price of his betrayal : Judas sells the Shepherd for thirty pieces of silver (Matthew 26:14-16; 27:3-10; Zechariah 11:4-13) -- The trail of silver -- The trail of blood -- Excursus three: Jesus the Shepherd in Matthew's Gospel -- Jesus and the temple charge : rebuilding the temple (Matthew 26:60-61; Zechariah 6:12) -- Jesus' crucifixion : the eschatological signs (Matthew 27:51-53; Zechariah 14:4-5) -- Jesus on the Mount of Olives : the Shepherd King (Matthew 21:1-11; 24:3; 26:30-56; Zechariah 9:9; 13.7; 14:4-5) -- Conclusion: Matthew's use of Zechariah